Why do those who watch Netflix, watch Netflix: engagement experiences of young Mexicans watching the streaming platform that revolutionized audiovisual consumption - Benavides Almarza, Cristóbal Fernando (2021)
The massification of streaming platforms, specifically Netflix, has modified the consumption patterns of an increasingly active and empowered audience when it comes to choosing how, when and what content to watch. This behavioral pattern has generated the exploration of new mechanisms to know in greater detail and depth the motivations and emotions that people have when they face audiovisual content and platforms. The measurement of engagement offers adequate information to predict those behaviors that condition consumption, as well as some characteristics that cause loyalty to a brand and willingness to pay for a service. This paper describes, through a quantitative factor analysis, the engagement experiences that 574 Mexican millennials have when using Netflix. It was established that when using Netflix, experiences related to socialization, entertainment and reflection on new topics stand out. This would indicate that beyond entertainment, it generates other types of attributes that are typically associated with it.